PEMETAAN MEDIA LUAR RUANG PADA PELAKSANAAN PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU (PILGUBRI) TAHUN 2013 DI KOTA PEKANBARU - ', Hasanuddin; Syamsuadi, Amir (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
The participation of candidates in local elections the democratic party is the dominant of the voteto win the political competition . Various attempts were made to improve the participants' tendencyto choose politics . Implementation of the election for governor and vice governor of Riau Provincein 2013 can not be separated from political activities such as marketing activities undertaken byall partner candidates for governor and vice governor of Riau Province .This study refers to the mapping ( mapping ) use outdoor media conducted by the regional headcandidates in the election of governor and vice governor of Riau Province in 2013 , especially inthe city of Pekanbaru . This study used a qualitative research approach ( qualitative research ) .The data will be used consists of two types of data , namely , the primary data , the data is obtaineddirectly from respondents and observations that have been conducted and secondary data , ie dataobtained from documents related to the study .Based on the results of the study concluded that the outdoor media used by candidates and prospectivecandidates of governor and vice governor of Riau Province in 2013 was in the form of billboards, billboards , banners and banner . The outdoor media widely installed in strategic areas inthe city of Pekanbaru as junction region , area shopping centers , bridge district , area attractions, and hospitality areas .Keywords : Mapping , Outdoor Media , Pilgubri 2013